Pharmacological role of efflux transporters: Clinical implications for medication use during breastfeeding - Ahmadzai, Hilai; Tee, Lisa; Crowe, Andrew (Baishideng Publishing Group Inc, 2014)
The World Health Organisation recommends exclusive breastfeeding for the first six months of an infant’s life and in combination with solid food thereafter. This recommendation was introduced based on research showing numerous health benefits of breastfeeding for both the mother and the infant. However, there is always concern regarding the transfer of medications from mother to their breastfed baby via milk. Pharmacokinetic properties of a drug are usually used to predict its transferability into breast milk. Although most drugs are compatible with breastfeeding, cases of toxic drug exposure have been reported. This is thought to be due to active transport mechanisms whereby efflux transporter proteins expressed in the epithelial cells of the mammary gland actively secrete drugs into milk. An example of such efflux transporters including the breast cancer resistance protein which is strongly induced during lactation and this could result in contamination of milk with the substrates of this transporter which may place the suckling infant at risk of toxicity. Furthermore, there is little known about the substrate specificity of most efflux transporters as we have highlighted in this review. There also exists some degree of contradiction between in vivo and in vitro studies which makes it difficult to conclusively predict outcomes and drug-drug interactions.